Nutritional support and dietary interventions following esophagectomy: challenges and solutions - Paul M; Baker M; Williams RN; Bowrey DJ (Nutrition and Dietary Supplements, 2017)
Melanie Paul, Melanie Baker, Robert N Williams, David J Bowrey Department of Surgery, Leicester Royal Infirmary, Leicester, UK Background and aims: Provision of adequate nutrition after esophagectomy remains a major challenge. The aims of this review were to describe the challenges facing this patient population and to determine the evidence base underpinning current nutritional and dietetic interventions after esophagectomy. Methods: Medline, Embase and CINAHL databases were searched for English language publications of the period 1990–2016 reporting on the outcome of nutritional or dietetic interventions after esophagectomy or patient-related symptoms. Results: Four studies demonstrated that early reintroduction of oral fluids was safe and was associated with a shorter hospital stay and ileus duration. One of three studies comparing in-hospital enteral nutrition against usual care showed that enteral feeding was well tolerated and was associated with a shorter hospital stay. Eight studies comparing enteral with parenteral nutrition showed similar surgical complication rates. Enteral feeding was associated with a shorter duration of ileus and lower health care costs. In hospital, all types of enteral access (nasoenteral, jejunostomy) were equivalent in their safety profiles. Cohort studies indicate that technical (tube dysfunction) and feed (diarrhea, distention) problems were common with jejunostomies but are easily managed. The mortality risk associated with jejunostomy in hospital is 0.2% (reported range 0%–1%), principally due to small bowel ischemia. There have been no reports of serious jejunostomy complications in patients receiving home feeding. One study demonstrated the advantages of home feeding in weight, muscle and fat preservation. Studies reporting 12 months or more after esophagectomy indicate a high frequency of persistent symptoms, dumping syndrome 15%–75% (median 46%), dysphagia 11%–38% (median 27%), early satiety 40%–90% (median 65%) and reflux 19%–61% (median 29%). Conclusion: Patients should resume oral intake as soon as possible after surgery. In hospital, all forms of enteral access appear to be safe. Out of hospital, the ability to provide home feeding by feeding jejunostomy is likely where meaningful nutritional improvements can be made. Improving nutrition and related quality of life in the early months might improve the long-term outcome. Keywords: esophagectomy, enteral nutrition, nutrition, nutritional status, weight